Streptokinase is dispensable in Streptococcus dysgalactiae subspecies equisimilis infections of human dendritic cells - Katharina E. Folz; Nikolai Siemens (Scientific Reports)
Abstract In recent years, increased numbers of severe Streptococcus dysgalactiae subsp. equisimilis (SDSE) infections, including necrotizing soft tissue infections (NSTIs), have been reported. One of the main virulence factors of SDSE is streptokinase (Ska). Ska promotes bacterial spread in the tissue through Ska-plasminogen interactions and subsequent activation of plasminogen to plasmin. In this study, the impact of streptokinase on SDSE infections of human monocyte-derived dendritic cells (moDCs) was investigated. MoDCs were infected with SDSE strain S118 and its isogenic mutant lacking streptokinase. All infections were performed with and without human serum to compare direct Ska-mediated as well as plasmin activity-related effects. Intracellular killing kinetics, moDC viability and maturation, as well as the release of pro-inflammatory cytokines were assessed. Irrespective of the strain and experimental conditions, the bacteria were equally phagocytosed and killed. MoDCs remained viable, readily matured and secreted equal amounts of cytokines in response to S118 as well as S118Δska infections. Our data demonstrate that moDCs response to SDSE infections is not affected by Ska or its respective plasminogen activating function.